Humans and Technology for Inclusive Privacy and Security. (December 2020) - Das, Sanchari; Gutzwiller, Robert S.; Roscoe, Rod D.; Rajivan, Prashanth; Wang, Yang; Jean Camp, L.; Hoyle, Roberto
Computer security and user privacy are critical issues and concerns in the digital era due to both increasing users and threats to their data. Separate issues arise between generic cybersecurity guidance (i.e., protect all user data from malicious threats) and the individualistic approach of privacy (i.e., specific to users and dependent on user needs and risk perceptions). Research has shown that several security- and privacy-focused vulnerabilities are technological (e.g., software bugs (Streiff, Kenny, Das, Leeth, & Camp, 2018), insecure authentication (Das, Wang, Tingle, & Camp, 2019)), or behavioral (e.g., sharing passwords (Das, Dingman, & Camp, 2018); and compliance (Das, Dev, & Srinivasan, 2018) (Dev, Das, Rashidi, & Camp, 2019)). This panel proposal addresses a third category of sociotechnical vulnerabilities that can and sometimes do arise from non-inclusive design of security and privacy. In this panel, we will address users' needs and desires for privacy. The panel will engage in in-depth discussions about value-sensitive design while focusing on potentially vulnerable populations, such as older adults, teens, persons with disabilities, and others who are not typically emphasized in general security and privacy concerns. Human factors have a stake in and ability to facilitate improvements in these areas.